The International Frontal Sinus Anatomy Classification (IFAC) and Classification of the Extent of Endoscopic Frontal Sinus Surgery (EFSS) - Wormald, Peter-John; Gößler, Ulrich (International forum of allergy & rhinology, 2016)
The frontal recess and frontal sinus anatomy can vary from simple to complex. The variations in the anatomy of the frontal recess and frontal sinus are considerable but almost all variations can be classified if the various cell patterns are analyzed. This consensus document was developed to improve the ability of the surgeon to understand these possible variations, plan the surgery, and communicate these complexities when teaching or reporting outcomes. Once the surgeon understands the anatomical pattern of the frontal sinus and recess cells, the extent of surgery can be planned. This document presents a classification of the extent of surgery based on the anatomical classification.